A comparative study on the taste quality of Mytilus coruscus under different shucking treatments. (30th June 2023) - Zhu, Shichen; Zhu, Lin; Ke, Zhigang; Chen, Hui; Zheng, Yadan; Yang, Peng; Xiang, Xingwei; Zhou, Xiaomin; Jin, Youding; Deng, Shanggui; Zhou, Xuxia; Ding, Yuting; et al.
Graphical abstract: Highlights: Amino acids, nucleotides and glycogen were key differential flavor components. Steaming shelling group shows the enriched flavor components and low nutrients loss. Structural equation modeling was applied to explore the taste interactions of mussel. Abstract: Shucking is an indispensable step in the preparation of cooked mussel products, as it facilitates the detachment of meat from the shell. In this study, we comprehensively investigated the effects of boiling, steaming, and microwaving on taste constituents in half-cooked mussel meat. Two-dimensional correlation spectroscopy revealed the key differential taste components of the different shucking groups. Structural equation modeling (SEM) indicated the positive effects of saltiness and bitterness on umami taste, while sweetness and sourness had negative effects on umami taste in half-cooked mussel meat. Furthermore, Glu, Asp, Ala, Arg, betaine, malic acid, succinic acid, glycogen, Cl −, Na +, K +, and PO3- 4 were quantitatively determined as the main taste compounds. The steaming shelling group had the most enriched taste components, with the highest equivalent umami concentration compared to the other shelling groups. Hence, steaming shucking may be favored due to abundant tastes and nutrients.